SAT0024 Enthesitis and dactylitis as the beginnnig stage of psoriatic arthritis. (1st June 2001) - Montilla, C; González, CM; López-Longo, FJ; Moreno-Zazo, M; Castillo, R; Caro, N; Cebrián, L; González-Montagut, C; Gómez, S; Monteagudo, I; Carreño, L
Abstract : Background: Enthesitis and dactylitis are characteristic features of psoriatic arthritis and the others spondyloarthropathies. Both may appear from the onset of the disease. Objectives: To analize the clinical characteristic of a population of patients with psoriatic arthritis who presented enthesitis and dactylitis as their only clinical symptoms at the onset of the disease. Methods: We have studied a group of 204 patients diagnosed with psoriatic arthritis following the Moll and Wright criteria, selecting only those who expressed either Enthesitis or dactylitis as initial symptoms of the disease. Results: Twenty-eight patients (14%) proved to have Enthesitis or dactylitis 21 enthesitis, 7 dactylitis and 1 Enthesitis and dactylitis as disease onset, and seventeen were men (60.7%). The mean age of psoriatic arthritis onset was 38 years (range: 17–58). The mean time from Enthesitis and dactylitis onset and the Moll and Wright criteria was 6 months (range: 1–180). Enthesitis was most frequent in achilles tendon (81%) and the plantar fascia (72.7%). Twenty patients (71.4%) presented arthritis involving peripheral joints, 4 (14.3%) presented and axial skeleton distribution, and the remaining (14.3%) showed a mixed peripheral and axial distribution. Conclusion: Enthesitis and dactylitis are initial clinical features of psoriatic arthritis, even though the majority of the patients with these symptoms at the beginning of the disease evolve towards a peripheral arthritis pattern.